IDENTITAS, POLITIK TUBUH PEREMPUAN DAN MEDIA TELEVISI - Widjajanti M. Santoso (Research Centre for Population, Indonesian Institute of Sciences, 2010)
Television is not only a powerful medium but also provides promising jobs for a lot of people from actress and actors to supporting system such as directors, scripts writers and talent scouting. Accordingly, sinetron is important subject of studies. There are a lot of critics against sinetron, as it shows traditional role of men and women, good and bad. But Indonesia s soap opera or sinetron tend to shows women as violence doers and men have limited power toward her. Women do violence in the name of love and family. Regarding the powerful iconic ability, sinetron has potential to educate and to disseminate ways to solve contemporary social situation face by Indonesian. This role actually is not something new, as in the New Orde, sinetron were used for development purpose. This has not yet becoming a perspective or behaviour toward the sinetron as powerful medium.Keywords: Gender, Soap opera, television, identity, violence